A Review of Formal and Informal Regulations in the Nordic Influencer Industry. - Abidin, Crystal; Hansen, Kjeld; Hogsnes, Mathilde; Newlands, Gemma; Nielsen, Mette Lykke; Nielsen, Louise Yung; Sihvonen, Tanja (2020)
This article provides a systematic review of laws, guidelines, and best practices related to the Nordic influencer industry as of the year 2020. We highlight some nuanced differences or shortfalls across Denmark, Finland, Norway, and Sweden, and give some policy rec-ommendations to national governments and industry in order to maintain a professional Nordic standard. The article identifies a degree of social, cultural, and economic coher-ence in the Nordic context that allows for the Danish, Finnish, Norwegian, and Swedish influencer industries to be viewed as a collaborative entity. It then reviews the status of income and tax procedures, and the regulation of commercial disclosures for influencers in the Nordic region. It is hoped that this research contributes to strengthening the integ-rity and rigour of the Nordic influencer industry to serve as a model for other regional networks of influencers.